Tactical Study of Care Originating in the Prehospital Environment (Tacscope): Acute Traumatic Coagulopathy on the Contemporary Battlefield. (September 2016) - Gerhardt, Robert T.; Glassberg, Elon; Holcomb, John B.; Mabry, Robert L.; Schreiber, Martin B.; Spinella, Philip C.
ABSTRACT: Background: Uncontrolled major hemorrhage and delayed evacuation remain substantial contributors to potentially survivable combat death, along with mission, environment, terrain, logistics, and hostile action. Life-saving interventions and the onset of acute traumatic coagulopathy (ATC) may also contribute. Objective: Analyze US casualty records from the DoD Trauma Registry, using International Normalized Ratio (INR) of 1.5 for onset of ATC. Methods: Retrospective cohort study from September 2007 to June 2011, inclusive. Independent variable was INR. Primary dependent variables were transfusion volume, massive transfusion (MT) defined as >10 units RBC/fresh whole blood in first 24 h, and 30-day survival. We used T test and chi-square analysis. Our IRB reviewed and exempted this study. Results: In total, 8, 913 cases were available. Fifty one percent had complete data with INR. Of excluded cases, 98.9% survived, average injury severity scales (ISS) was 7 (IQR 1–8), and less than 1% received MT. Among included cases, 98.5% survived, average ISS was 10 (IQR 2–14), average INR was 1.16 (CI95 1.14–1.17), and 2.7% received MT. There were 383 cases with ATC (8.4%). After stratification, we found that ATC cases were more likely to die (odds ratio (OR) 28, CI 16–48), receive MT (OR 9.6, CI 6.4–14.4), and were acidotic (pH 7.27 (7.24–7.31) vs. 7.38 (7.38–7.39)). Other significant differences included Injury Severity Score, Revised Trauma Score, blast mechanism, and penetrating injury. Conclusion: ATC is substantially associated with greater injury severity, MT, and mortality. Prehospital identification of MT casualties may expedite triage and evacuation, and enable remote damage control resuscitation to delay ATC onset and improve outcomes.